Anomali Cinta: Kedaulatan Allah yang Bebas dalam Mencintai Ciptaan-Nya - Sitorus, Yohannes Ali Sandro (STT Iman Jakarta, 2024)
Every faithful person understands that God is a loving entity and loves His creation tremendously. His actions are understood as a manifestation of true love. However, is God's love a categorical or normative thing? Does God's love equate to the absence of hatred or